Conditional Jump Dynamics in the Stock Prices of Alternative Energy Companies - Lee, Yen-Hsien; Huang, Ya-Ling; Wu, Chun-Yu (International Journal of Energy Economics and Policy, 2013)
This paper researches the abnormal information in the WilderHill Clean Energy Index (ECO) and NYSE Arca Technology Index (PSE) by using an autoregressive conditional jump intensity model in Skew Generalized Error Distribution (ARJI-SGED). The research period is from 3 January 2001 to 31 January 2011. We also test the diffusion-jump variance on the PSE and ECO. The empirical result indicates that there are jump phenomena in clean energy and technology companies. The oil price impacts on clean energy and technology companies. Moreover, the PSE has higher levels of volatility clustering than the ECO. These results show that the distributions of PSE return are skewed slightly to the left and fat-tailed. These also mean that jump variance plays a crucial role in market volatility indices. Keywords: Clean Energy; Abnormal Information; ARJI-SGED Model JEL Classifications: C2; G1; Q42